Pendekatan Trauma Healing Untuk Mengatasi Pathological Grief Pada Anak Usia Remaja Yang Ditinggal Mati Orang Tuanya - Revinola Enjelvestia Parebong (Institut Agama Kristen Negeri Kupang, 2021)
When the death of a parent occurs, the child will experience a sense of loss that will eventually result in grief. The experience of loss has an impact on the lives of adolescents, both physically, emotionally and spiritually because of the child's grief over the death of his parents. In psychology, the loss experienced by an individual over the death of a loved one is explained through the concept of grief. In this case, grief is divided into two types, namely: normal grief and pathological grief. Normal grief is a normal grief reaction experienced by individuals and ends in a not too long time. While pathological grief is an abnormal grief reaction because it traps people so that they are unable to escape from their emotional attachment to the person who left them. Circumstances like that ultimately make a person traumatized so that a recovery process is needed for people who experience pathological grief. This paper aims to explain the trauma healing approach to overcome pathological grief in adolescent children who have lost their parents. This study uses a qualitative literature method through a literature study with a content analysis approach. The results of this study are to determine the definition of pathological grief and trauma healing; symptoms of pathological grief experienced by teenagers due to the death of their parents; and knowing how to overcome pathological grief by using a trauma healing approach.